Determinants of life satisfaction and self-rated health in Iranian children and adolescents: a structure equation model - Pooneh Angoorani; Zohreh Mahmoodi; Hanieh-Sadat Ejtahed; Ramin Heshmat; Mohammad Esmaeil Motlagh; Mostafa Qorbani; Roya Kelishadi (BMC, 2022)
Abstract Background Life satisfaction (LS) and self-rated health (SRH) are related with health outcomes. It is expected that these items are also related to healthy behaviors. Therefore, this study was conducted in order to find out the main determinants of LS and SRH in nationwide representative sample of Iranian children and adolescents. Methods This study was performed on 13,834 students aged 7-18 years who were selected by multistage, stratified cluster sampling method from 30 provinces of Iran. Life satisfaction and SRH were assessed through a questionnaire based on World Health Organization-Global School-based Student Health Survey protocols. Path analysis was applied to evaluate the relationships among the study variables using the structural modeling. Results Life satisfaction was directly affected by age (− 0.037 in boys & -0.028 in girls); sedentary time (0.055 in boys & 0.048 in girls); school satisfaction (0.249 in boys & 0.250 in girls); and well-being (0.186 in boys & 0.176 in girls). Self-rated health was directly affected by LS (0.28 in boys & girls) and school satisfaction (0.21 in boys & 0.22 in girls); and indirectly affected by age (− 0.046 in boys & -0.017 in girls); sedentary time (− 1.99 in boys & -0.145 in girls); family size (− 0.005 in boys & -0.014 in girls); and socio-economic status (0.015 in boys & 0.058 in girls). Conclusions This study indicated that school satisfaction had the greatest positive direct effect on both LS and SRH.